MOSAIC OF ORIGINAL CULTURAL VALUES OF SERBS OF THE KOSOVO MARITIME (Heritage, 2020)
Customs, as a social phenomenon, in the foreground means the existence of order and morality in a community of people, which presupposes a predetermined rule, behavior and respect for its specific unwritten laws. Specific characteristics and manifestations of interpersonal relationships and behavior are visible in their speech, creativity and artistic expression, architecture and culture of housing, the way they dress and make festive costumes, then in the celebration of family, church, school and other holidays and events. The richness and diversity of such characteristics and customs becomes a criterion for the development of the ethical consciousness of a society, a person or a family, as well as a measure of the level of their culture. The freedom of a moral person is reflected, in addition to good will, in the correct attitude and understanding of ordinary manifestations and the emotions of members of one social community conditioned by them. Each culture develops its own spiritual and material heritage and thus defines its identity and character, as its own way of understanding the world. The Serbs of Kosovo Pomoravlje are dedicated guardians of all Serbian historical traditions, especially those about Kosovo. On that fateful task, they regularly had support in their church and clergy, as well as in the dedicated work and creativity of their teachers, such as Zarija Popović and Atanasije Urošević.
Keywords: culture, art, folk creation, freedom, Kosovsko Pomoravlje, Draganac, Zarija Popović, Atanasije Urošević.